Navigating dual frontlines: transforming clinical urgency and academic excellence through distributed leadership - Mingyan Shen; Zhixian Feng; Pengxia Wan; Fangchi Liu (BMC Medical Education)
Abstract Introduction Double-qualified nursing educators (DQNEs) face significant challenges in balancing clinical and teaching duties. Distributed leadership offers a potential solution to these challenges by sharing responsibilities among team members. We studied how DQNEs respond to distributed leadership training and its impact on their dual-role performance. Methods Guided by descriptive phenomenology, we conducted semi-structured interviews with 16 DQNEs between October and November 2024, after an 18-month distributed-leadership training programme.We conducted thematic analysis of semi-structured interviews, following COREQ guidelines to ensure research quality. Results Our analysis revealed two main themes. First, distributed leadership training improved participants' confidence, teamwork, and time management. DQNEs reported better role balance and more effective delegation. Second, we found that traditional hierarchies and cultural norms posed implementation challenges. Success factors included clear communication, defined roles, and ongoing leadership support. Conclusion Distributed leadership training shows promise in helping DQNEs manage their dual roles while promoting team efficiency. The approach requires careful attention to cultural and organizational barriers. These findings offer insights for adapting distributed leadership across different clinical and educational settings.